Vitamin D improves endothelial dysfunction and restores myeloid angiogenic cell function via reduced CXCL-10 expression in systemic lupus erythematosus - Reynolds, John A.; Haque, Sahena; Williamson, Kate; Ray, David W.; Alexander, M. Yvonne; Bruce, Ian N. (Scientific reports, 2016)
Patients with systemic lupus erythematosus (SLE) have accelerated cardiovascular disease and dysfunctional endothelial repair mechanisms. Myeloid angiogenic cells (MACs), derived from circulating monocytes, augment vascular repair by paracrine secretion of pro-angiogenic factors. We observed that SLE MACs are dysfunctional and secrete pro-inflammatory cytokines. We also found that the vitamin D receptor was transiently expressed during MAC differentiation and that in vitro , calcitriol increased differentiation of monocytes into MACs in both SLE and in a model using the prototypic SLE cytokine, interferon-alpha. The active form of vitamin D (calcitriol) restored the SLE MAC phenotype towards that of healthy subjects with reduced IL-6 secretion and normalised surface marker expression. Calcitriol also augmented the angiogenic capacity of MACs via the down-regulation of CXCL-10. In SLE patients treated with cholecalciferol for 12 weeks, the improvement in endothelial function correlated with increase in serum 25(OH)D concentrations independently of disease activity. We also show that MACs were able to positively modulate eNOS expression in human endothelial cells in vitro, an effect further enhanced by calcitriol treatment of SLE MACs. The results demonstrate that vitamin D can positively modify endothelial repair mechanisms and thus endothelial function in a population with significant cardiovascular risk.